Correlation between serum KL-6 level and severity of SARD-related ILD - Emmy Pranggono; Alvy Syukrie; Valentine Natasya Moenadri; Sumartini Dewi (Faculty of Medicine Universitas Padjadjaran, 2022)
Objective: To understand the correlation between serum KL-6 level and severity of SARD-related ILD in Indonesia.Method: This was a cross-sectional study to evaluate the correlation between serum KL-6 level and Interstitial Lung Disease (ILD) severity based on Chest High-Resolution Computed Tomography (Chest HCRT) among patients with Systemic Autoimmune Rheumatic Disorders (SARD) who visited the Rheumatology Clinic of Dr. Hasan Sadikin General Hospital during the period of January 2019 to February 2020. Secondary data were retrieved from a study on the Effects of Ciplukan Herbs on Organ Fibrosis. KL-6 serum concentration was measured from stored biological material and the correlation between the serum KL-6 level and ILD severity was analyzed by Rank Spearman's test.Results: Thirty-four patients participated in this study with a median age of 37 years-old. Most of the participants were female (94.1%), Sundanese (64.7%), and had systemic sclerosis as an underlying disease (48.5). The median serum KL-6 level was 57.1 U/ml (21.6-444.1). Most participants belonged to severe ILD group (58.8%) with a mean serum KL-6 level of 65.1±48.9 U/ml. The highest mean serum KL-6 level (111.6±121.8) was observed in the moderate ILD group comprising of 32.4% of the participants. The remaining 11.8% participants belonged to mild ILD group with a mean serum KL-6 level of 61.1±24.9 U/ml. Serum KL-6 level was demonstrated to have a weak correlation with ILD severity (r=-0.229, p=0.193).Conclusion. There is an insignificant weak correlation between serum KL-6 level and ILD severity based on chest HRCT in SARD patients.